The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jcsr.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical assessment of slab-interaction effects on the behaviour of steel-concrete composite joints

Abstract: In current design practice for seismic resistant steel braced frames, general rules and standard provisions are\ud aimed to ensure a structural behaviour for beam-to-column joints of non-braced spans as close as possible to\ud perfect hinges. This is done to prevent any kind of interaction with the bracing systems, in particular under\ud horizontal loads. However, the global performance of composite joints is markedly affected by the structural\ud interaction between the concrete slab and the steel components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Among them, the steel-concrete composite frame is currently a widespread structural system in multistory and high-rise buildings since it combines the advantages of both steel and concrete frames, thus leading to, in many cases, a reduction of costs and optimization of the structural performance [16,17]. The mechanical behavior of composite frame systems including experimental and theoretical research, has been reported in detail over the last few decades [18][19][20][21], and previous research, has demonstrated that the presence of reinforced concrete (RC) slabs is beneficial to the flexural capacity, stiffness and lateral stability of steel beams, which also improves the seismic performance of the frame [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the steel-concrete composite frame is currently a widespread structural system in multistory and high-rise buildings since it combines the advantages of both steel and concrete frames, thus leading to, in many cases, a reduction of costs and optimization of the structural performance [16,17]. The mechanical behavior of composite frame systems including experimental and theoretical research, has been reported in detail over the last few decades [18][19][20][21], and previous research, has demonstrated that the presence of reinforced concrete (RC) slabs is beneficial to the flexural capacity, stiffness and lateral stability of steel beams, which also improves the seismic performance of the frame [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2019, 9, x FOR PEER REVIEW 2 of 24 stiffness and lateral stability of steel beams, which also improves the seismic performance of the frame [22,23]. However, under vertical and seismic loads, tensile stresses and cracks may occur in the concrete slab at beam ends where a hogging moment exists, which has always been a critical issue hindering the widespread application of steel-concrete composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the numerical simulation is another effective approach to investigate the seismic performance of structures, and significant progress has been made in the development of nonlinear analysis programs for evaluating the seismic performance of steel-concrete hybrid structures [17][18][19][20][21]. Accordingly, on the basis of experimental results, the numerical investigation on the seismic performance of this hybrid structure was conducted in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Shear connection ratio of a composite beam depends on the number of connectors in the beam. A full shear connection in steel-concrete composite beam is recommended by most of the researches as it will gives higher ultimate strengths than partial shear connection [31][32][33][34][35][36]. This also proved by Kwon et al that the strength, stiffness, and deformation capacity of the composite beams increased with increasing shear-connection ratio [29].…”
Section: Effect Of Bolt Spacing Number Of Bolts (Shear Connection Ramentioning
confidence: 88%